Classroom Interaction in the Teaching of English at a Private High School in Indonesia - Siti Mukaromah; Henrikus Joko Yulianto (Universitas Negeri Semarang, 2023)
This study aimed to analyze the indirect and direct talk, response and initiation, and silence of teacher and student interaction in the teaching of English. This research employed an exploratory mixed method. The subject of this study was the English teacher and twenty-seven students of an English class of eleven grade in Madrasah Aliyah Futuhiyyah-2 Mranggen. The data was collected using observation, interviews, and questionnaires. The talk was analyzed using Flanders's theory (1965), modified by (Amatari, 2015; Sharma & Tiwari, 2021). The result of this study showed that the average value of activities carried out by teachers during learning is 62.44%. The average score of student activity was 29.16%. The total value of teacher and student activities is 91.6%. The value of silence is 8.33%. The percentage of teacher and students talking in the classroom interaction indicates a high tendency to accept feelings and praise or encouragement, lecturing, and responses. The indirect and direct talk implemented in classroom interactions showed that indirect 41,62% was higher than direct talk 20,82%. The response and initiation showed that the students pay attention well to the teacher and sometimes give initiation. The domineering talk caused silence showed that the use of silence was low. Viewed from the number of average scores produced by teacher of 62.44% and student talk of 29.16%, it can be concluded that the percentage of teachers talk is higher than students. This research could help teachers to evaluate their teaching activities. Additionally, for students, the findings of this study can increase participation using the initiation category.